2007
DOI: 10.1007/s00132-007-1057-8
|View full text |Cite
|
Sign up to set email alerts
|

Serumfreie Kultivierung von Osteoprogenitorzellen und Osteoblasten zur Testung von Biomaterialien

Abstract: The aim of the study is to describe a model for testing biocompatibility of implant materials. Usually cells do not bind the biomaterial surface itself via integrins but adsorbed proteins of blood or interstitial fluids. To eliminate the influence of serum proteins on cell adhesion to the test materials we cultivated osteoprogenitor cells and osteoblasts with a serum replacement or with fetal calf serum, but seeded them likewise without serum or serum replacement on cell culture polystyrene, sandblasted titani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Beside their importance in cell–cell interactions, the other major function of membrane integrins is their contribution toward the anchoring of the cell to the proteins of the extracellular matrix. The interactions are based on short peptide sequences that are constituents of many proteins of the extra cellular matrix and that interact with the membrane integrins 2, 3. This short sequence is found in proteins such as fibronectin, vitronectin, collagen, and osteopontin and is typically denoted the short form RGD.…”
Section: Introductionmentioning
confidence: 99%
“…Beside their importance in cell–cell interactions, the other major function of membrane integrins is their contribution toward the anchoring of the cell to the proteins of the extracellular matrix. The interactions are based on short peptide sequences that are constituents of many proteins of the extra cellular matrix and that interact with the membrane integrins 2, 3. This short sequence is found in proteins such as fibronectin, vitronectin, collagen, and osteopontin and is typically denoted the short form RGD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a serum-free pOB culture was generated, which provided a continuous, acceptable viability of more than 85%. A serum-free osteoblast progenitor cell model for biomaterial testing was introduced by Duewelhenke and Eysel (2007) [ 38 ]. It has been shown that fetuin, likewise to the well-known adhesion proteins fibronectin and vitronectin, can function as an adhesion promoter on titanium materials.…”
Section: Discussionmentioning
confidence: 99%